The economic and social modernization of the Republic of Korea (Council on East Asian Studies, Harvard University, 1980)
This book examines the growth and structural transformation of the Korean economy, the foreignsector and aid urbanization rural development, the role of entrepreneuship population policy and demographic transition and education.